Напружено-деформований стан та залишковий ресурс залізобетонних конструкцій, підсилених за дії навантаження - Хміль, Роман Євгенович (Національний університет "Львівська політехніка", 2021)
Дисертаційна робота присвячена вирішенню наукової проблеми встановлення дійсного напружено-деформованого стану залізобетонних згинаних та стиснуто-згинаних конструкцій, підсилених за дії навантаження і створенню розрахункових методик для проєктування та оцінювання надійності та залишкового ресурсу таких конструкцій. Проведено експериментальні дослідження арматурних стержнів, залізобетонних згинаних та стиснуто-згинаних елементів, підсилених за одночасної дії навантаження диференційованого рівня. На основі силової та деформаційної розрахункових моделей нормального перерізу розроблені методики розрахунку залізобетонних згинаних та стиснуто-згинаних елементів, підсилених за дії навантаження. Розроблено принципові моделі оцінки ймовірності безвідмовної роботи залізобетонних конструкцій, підсилених за дії навантаження, адаптовані до чинних норм проєктування та існуючої методики оцінки надійності нових проєктних конструкцій. Принциповими особливостями розроблених моделей є пропозиція врахування стохастичного параметра рівня навантаження конструкції в момент підсилення, а також використання деформаційної моделі її розрахункового перерізу. Виходячи з передумов оцінки ймовірності безвідмовної роботи, запропоновано підходи до визначення залишкового ресурсу підсилених конструкцій. Диссертация посвящена решению научной проблемы установления действительного напряженно-деформированного состояния железобетонных изгибаемых и сжато-изгибаемых конструкций, усиленных за действия нагрузки и создание расчетных методик для проектирования и оценки надежности и остаточного ресурса таких конструкций. Проведены экспериментальные исследования арматурных стержней, железобетонных изгибаемых и сжато-изгибаемых элементов, усиленных при одновременном действии нагрузки дифференцированного уровня. На основе силовой и деформационного расчетных моделей нормального сечения разработаны методики расчета железобетонных изгибаемых и сжатоизгибаемых элементов, усиленных за действия нагрузки. Разработаны принципиальные модели оценки вероятности безотказной работы железобетонных конструкций, усиленных за действия нагрузки, адаптированные с действующими нормами проектирования и существующей методики оценки надежности новых проектных конструкций. Принципиальными особенностями разработанных моделей является предложение учета как стохастического параметра уровня нагрузки конструкции в момент усиления, а также использование деформационной модели ее расчетного сечения. Исходя из предпосылок оценки вероятности безотказной работы предложены подходы к определению остаточного ресурса усиленных конструкций. The dissertation is devoted to the research of reinforced concrete bending and compressed-bending structures, which are strengthened by increasing the cross section of reinforcement or reinforcement and concrete at one time under loading. The introduction substantiates the relevance, purpose and objectives of research, general characteristics and scientific novelty as well as the practical value of research. The first section reviews the technical literature on research issues, namely: the existing methods of reinforcing reinforced concrete bending and compressed-bending elements, The analysis of stress-strain state of reinforced concrete structures, methods of forecasting (estimating) remaining resource of strengthened structures in operating conditions are presented. In addition, the reliability analysis of strengthened reinforced concrete structures, the state of the calculation of the actual reliability of the elements after reinforcement. The second section is devoted to the development of methods and programs for experimental research of reinforced concrete bending and compressed-bending elements, reinforcement of which is performed by the most common methods, namely increasing the cross section of reinforcement, reinforcement and concrete (clamp). The presence of the load on the structure allows us to simulate the operation of the strengthened structure in accordance with the actual operating conditions and the device of the reinforcement. An integral part of the program of experimental research is the study of reinforcing bars (50 samples) and the common action of concrete of the existing and additional cross section of reinforced concrete structures; performed under load. The third section presents the results of experimental research of bending and compressed-bending reinforced concrete elements: not strengthened and strengthened with additional reinforcement and additional reinforcement and concrete both (reinforced concrete jacket) with and without preloading during strengthening. On the example the strengthening method by making of reinforced concrete jacket, as the most difficult to perform and as a general case of strengthening of reinforced concrete structures by increasing the cross section, some results were presented. The stressstrain state of the strengthened reinforced concrete beams and columns can be divided into three stages. At the first stage, after the installation of the reinforced concrete jacket, the increase in the deformation of the main reinforcement was significantly reduced, as on additional reinforcement and concrete. The second stage starts with the achievement of yield strength in the stretched reinforcement of the main or additional bars. This was accompanied by an increase in the deformation of the main reinforcement and deflections. The third stage is failure. The fourth section presents calculation methods of remaining strengthened reinforced concrete structures bearing capacity. An important difference between the calculation of the force model from code of DSTU B V.3.1-2: 2016 from the deformation model of calculation by DSTU B V.2.6-156: 2010 is that it does not allow to estimate the stress-strain state of the structure at any cross section layer and any stages but only in the limit state. According to the results of theoretical researches it is offered and experimentally confirmed that at maintenance of reliable anchoring of additional bars, common action of bars and concrete of the main and additional part of cross sections, we can recommend using as criterion of exhaustion of bearing capacity of complex cross section yield achievement of all reinforcing bars. The fifth section describes the computer modeling of strengthened r/c beams in the application software, which were developed by the finite element method (FEM). Algorithms for creating a geometrical and physical model, a loading model of strengthened structure, which would reflect the real conditions of their operation and reinforcement, are proposed. The beam finite-element model were developed in two software packages. The calculation was performed taking into account the physical nonlinearity of materials and their calculated physical and mechanical properties, which were introduced into the adopted of deformation relationship. A comparative analysis of the research results with the calculated values of the ultimate bending moments obtained in accordance with the calculations according to the design codes is performed. Satisfactory convergence of adjacent values was recorded. The sixth section presents the results of development and testing of the proposed methods, as well as analysis of the obtained values of qualitative and quantitative indicators of reliability – reliability index β of bending and compressedbending structures, strengthened by increasing the cross section of reinforcement, both reinforcement and concrete under load. The level of load acting at the time of strengthening is considered as an additional random value. Based on the analysis of the obtained values of reliability indexes β and probability of failure-free operation P(β) the approaches to determining the remaining resource of reinforced structures are proposed.
Напряженно-деформированное состояние и остаточный ресурс железобетонных конструкций, усиленных за действия нагрузки
Stress-strain state and remaining resource of reinforced concrete structures reinforced under load
Keywords: залізобетонна балка; колона; підсилення; рівень навантаження; стрижнева арматура; композитна стрічка; обойма; методика розрахунку; оцінка надійності; ймовірність безвідмовної роботи; железобетонная балка; колонна; усиление; уровень нагрузки; стержневая арматура; композитная лента; обойма; методика расчета; оценка надежности; вероятность безотказной работы; reinforced concrete beam; column; strengthening; level of loading; reinforcing bars; composite strip; jacket; design method; reliability assessment; probability of failure-free operation; remaining resource; 624.012.45